Numerical simulations of coastal water qualities - Yip, Kenny Yeow Seng. (2013)
Eutrophication has been on the rise significantly in the recent years due to an increase in the amount of human activity such as agriculture, manufacturing, fertilizers and pesticides which contribute significantly to the eutrophication from surface runoff of rainfalls. Eutrophication causes the oxygen level in the affected waters to decrease significantly and this results in huge loss of marine life in those waters.